ENERGY PRODUCTION OF A HYBRID SOLAR ELECTRIC VEHICLE CHARGING SYSTEM - RÓBERT ISTÓK (Journal of Engineering Studies and Research)
As a consequence of increasing electric vehicle number, the number of electric vehicle chargers are increasing too. The main advantage of electric vehicle is the zero CO2 emission. One of the biggest advantage of solar electric vehicle charger built at Óbuda University is that offer the possibility to charge the electric vehicle with energy which are coming from a solar system. The system contains a solar part, an energy storage part and the electric vehicle charger part. The internet connection of the system gives the possibility to have real time information about the system. Continuous monitoring of the system, assure an overview on source and on amount of energy consumption.